Barriers to cleaning of shared latrines in slums of Addis Ababa, Ethiopia. - Kidist Hailu; Zewdie Aderaw Alemu; Metadel Adane (PLoS ONE, 2022)
Shared latrines and other shared sanitation facilities are vital for communities that lack private latrines. However, the cleanliness of shared latrines continues to be a problem in sub-Saharan Africa, including slums of Addis Ababa, Ethiopia. Investigating the barriers to cleaning of shared latrines may inform the future strengthening of comprehensive sanitation programs in slums of Addis Ababa, Ethiopia. Thus, a community-based unmatched case-control study was conducted among 100 case and 200 control households that were users of shared latrines from September to November 2017 in a slum district in Addis Ababa. Cases were those who had not cleaned their shared latrines and controls were those who had cleaned their shared latrines at least once during the week prior to data collection. Data were collected using a structured questionnaire and an on-the-spot-observational checklist and analyzed using bivariate (crude odds ratio [COD]) and multivariable (adjusted odds ratio [AOR]) unconditional logistic regression model. Variables having a p-value of less than 0.25 from the bivariate logistic regression analysis were retained into multivariable analysis. From the multivariable analysis, variables with p<0.05 were declared as factors significantly associated with barriers to cleaning of shared latrines. We found that about half 99 (49.5%) of shared latrines used by cases and almost one-third 32 (32.0%) of the shared latrines used by controls had visible cracks and spaces in the floor and slabs. The barriers to cleaning of shared latrines were found to be monthly household income of less than $55.60 USD (AOR = 1.80; 95%CI: 1.2-3.10), users feeling a lack of privacy during latrine use (AOR = 2.95; 95% CI: 1.60-5.43), no locking latch on the latrine door (AOR = 4.60; 95% CI: 2.43-8.79), inadequate ventilation of latrine (AOR: 4.88; 95% CI: 2.44-9.63), lack of regular monitoring of latrine by health extension workers (AOR = 2.86; 95%CI: 1.32-6.21) and a lack of enough water at home for cleaning the latrine (AOR = 4.91; 95% CI: 1.07-9.48). This study found several barriers to cleaning of shared latrines in slums of Addis Ababa. We recommend that stakeholders promote cleaning of shared latrines by designing programs to improve latrine privacy by adding or modifying the superstructure and including a door with locking latch, to make adjustments to the structure for better ventilation, to ensure regular monitoring of latrines by health extension workers and to make enough water consistently available for regular latrine cleaning.